2003
DOI: 10.1051/0004-6361:20031538
|View full text |Cite
|
Sign up to set email alerts
|

Doppler imaging of stellar surface structure

Abstract: Abstract. We present the first Doppler image of the single G0-dwarf HD 171488. As a 30-Myr young field star with a lithium abundance of ≈140-times that of the Sun and a rotation 20 times faster, it is hardly a "solar analog" but could be termed an "infant Sun". Its position in the H-R diagram suggests it to be in the rapid-braking phase just prior to arrival on the ZAMS. Our Doppler images from four spectral lines show a cool polar spot and various high-latitude spot features with a temperature contrast of 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
60
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 48 publications
15
60
0
Order By: Relevance
“…where the rotational period (P rot ) is nearly identical to the value of 1.3371 days found by Strassmeier et al (2003). With a periodogram analysis and a clean deconvolution algorithm (Roberts et al 1987) we found a period of 1.37 ± 0.12 days that is fully consistent with the value of Järvinen et al (2008), taking the limited time span of our data into account.…”
Section: Light Curve and Spot Modelingsupporting
confidence: 85%
See 2 more Smart Citations
“…where the rotational period (P rot ) is nearly identical to the value of 1.3371 days found by Strassmeier et al (2003). With a periodogram analysis and a clean deconvolution algorithm (Roberts et al 1987) we found a period of 1.37 ± 0.12 days that is fully consistent with the value of Järvinen et al (2008), taking the limited time span of our data into account.…”
Section: Light Curve and Spot Modelingsupporting
confidence: 85%
“…With only two photometric bands and the rather small amplitude of the light curve it is not easy to derive the spot temperature. Thus we preferred to fix the spot temperature, ΔT = 1500 K, close to the values found for high latitude spots by Strassmeier et al (2003) and Järvinen et al (2008) with DI technique, and let the spot area and location be free to vary. In order to minimize the degrees of freedom and still allowing the code to reproduce an asymmetric light curve, only two spots have been put on the photosphere.…”
Section: Light Curve and Spot Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…HD 171488 (V889 Her) is a young active G dwarf. Strassmeier et al (2003) found a photospheric temperature of 5830 K, a rotation period of 1.337 days, a mass of 1.06 ± 0.05 solar masses, a radius of 1.09 ± 0.05 solar radii, and an age of 30−50 Myr. Marsden et al (2006) find a rotation period of 1.313 days, a photospheric temperature of 5800 K, and a radius of 1.15 ± 0.08 solar radii.…”
Section: R58 Lq Lup and Hd 171488mentioning
confidence: 97%
“…Active longitudes show a high spot coverage stretching over a large area of the star, persisting for many months or years, which translates into several hundreds of stellar rotations. It is largely unknown whether their internal structure is variable, i.e., to what degree spots move, disappear, or form inside of Article published by EDP Sciences Strassmeier et al (2003).…”
Section: Introductionmentioning
confidence: 99%